2009
DOI: 10.1007/s10608-009-9281-7
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Cognitive Vulnerability-Stress Model of Depression in the Transition to Adolescence

Abstract: This study examined whether the cognitive vulnerability-stress model of depression may contribute to our understanding of the gender difference in depression in adolescence. Specifically, we examined emergent gender differences in depressive symptoms, cognitive style, and stress in the context of exposure, cognitive scar, and stress generation models. We also examined whether gender moderated the cognitive vulnerability-stress effects on depression. Participants were 366 youth from a community sample who compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
62
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 54 publications
(85 reference statements)
9
62
1
1
Order By: Relevance
“…This result contrasts with that obtained by Mezulis et al (2009), given that in their study the gender differences in depressive symptoms preceded the gender differences in cognitive style. A tentative explanation for these different results may lie in the different age range included in each study.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…This result contrasts with that obtained by Mezulis et al (2009), given that in their study the gender differences in depressive symptoms preceded the gender differences in cognitive style. A tentative explanation for these different results may lie in the different age range included in each study.…”
Section: Discussioncontrasting
confidence: 97%
“…In support of this hypothesis, some studies show that gender moderates the role of negative inferences as a predictor of depression, both alone (Calvete in press;Gladstone et al 1997) and when interacting with stressors (Mezulis et al 2009), and that sociotropy predicts levels of stressors in women but not in men (Shih 2006). Therefore, a final objective of this study was to examine whether sociotropy, negative inferences and exposure to social stressors account for the girls' higher rates of depressive symptoms, and whether predictive relationships among sociotropy, social stressors, negative inferences, and depression are moderated by gender.…”
Section: Is the Predictive Relationship Between Sociotropy And Depresmentioning
confidence: 96%
See 1 more Smart Citation
“…This is a well-supported finding with some research reporting a 70 % greater risk for women (Wang et al 2005). Mezulis et al (2010) partly relate the rise in MDD by age 18 to the greater rise in prevalence in young women (twice that of young men). Prior to age 18, males and females have fairly equivalent rates of the illness.…”
Section: Epidemiology Of Depressionsupporting
confidence: 54%
“…Prior studies have shown that women are more likely to report interpersonal stresses than men (Mezulis, Funasaki, Charbonneau, & Hyde, 2010;Rudolph & Hammen, 2003;Kendler, Thornton, & Prescott, 2001). From this, it can be assumed that either women are more sensitive in recognizing interpersonal conflicts, or they actually experience interpersonal NLEs more often.…”
Section: Introductionmentioning
confidence: 99%